Legitimate Prejudice in Legal Interpretation: Gadamer's Hermeneutics as an Analytical Framework - Sugeng, Sugeng; Aidy, Widya Romasindah (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
Legal interpretation is often influenced by certain prejudices or preconceptions that are regarded as legitimate in the process of understanding legal texts. These prejudices are not necessarily irrational or unfounded; rather, they form part of the interpreter's horizon, shaped by history, culture, and prior knowledge. This article explores the concept of legitimate prejudice within the realm of legal interpretation, using Hans-Georg Gadamer’s philosophical hermeneutics as its analytical framework. Gadamer’s approach offers a nuanced understanding of how meaning emerges through the fusion of horizons between the legal text and the interpreter’s situated perspective, highlighting the productive role of prejudice in the interpretive process. Gadamer's hermeneutics offers an approach that emphasizes the importance of dialogue between the text, the reader, and its historical context. In the context of legal interpretation, legitimate prejudice is not merely viewed as an obstacle but also as a constructive element that enables the creation of legal meaning that is more relevant to social dynamics. This article examines how Gadamer's